Caravela: A Novel Stream-Based Distributed. - Yamagiwa, Shinichi; Sousa, Leonel (Computer (00189162), 2007)
The authors describe the Caravela distributed computing environment, which offers tools for managing and programming I/O data in both local and remote devices. Caravela applies a proposed flow model for stream-based programming using graphics processing units. The model allows for sharing programs among network computers and executing the programs remotely, with data flowing through memory. It can be used for numeric computing, data mining, and physical simulations. The article mentions the use of XML files, DirectX, and HLSL.